Conceptual, pedagogical, cultural, and political dilemmas of implementing a constructivist workshop approach to teaching literacy. Issue 7 (2nd October 2016) - Porath, Suzanne L.
Abstract: Approached as an epistemology, implementing a constructivist workshop approach to literacy can challenge the traditional paradigm of teacher-focused instruction and transform to one where students construct knowledge together and learn through active engagement in authentic reading and writing. This study illustrated how two third-grade teachers managed the conceptual, pedagogical, cultural and political dilemmas they encountered when they began implementing a constructivist workshop approach to literacy. This study validates the disquiet and discomfort teachers may feel as they utilize new curriculum, illustrates that a workshop approach requires an understanding/articulation of personal and curricular pedagogical and epistemological foundations, and encourages administrators to recognize that teachers need time and space to take risks and reflect on their work.